Studies from a Retranslation Culture The Turkish Context - Berk Albachten, Özlem; Tahir Gürçağlar, Şehnaz (New Frontiers in Translation Studies, 2019)
This book highlights the unique history and cultural context of retranslation in Turkey, offering readers a survey of the diverse range of fields, disciplines, and genres in which retranslation has assumed a central position. Further, it addresses largely unexplored issues such as retranslation in Ottoman literature, paratextual positioning and marketing of retranslations, legal retranslation, and retranslation in music. As such, it makes a valuable contribution to the growing body of research on retranslation by placing special emphasis on non-literary translation, making the role of retranslation particularly visible in connection with politics and philosophy in Turkey. .